Occult Langerhans Cell Histiocytosis Presenting with Papillary Thyroid Carcinoma, a Thickened Pituitary Stalk and Diabetes Insipidus - Michael S. Gordon; Murray B. Gordon (Case Reports in Endocrinology)
Etiologies of a thickened stalk include inflammatory, neoplastic, and idiopathic origins, and the underlying diagnosis may remain occult. We report a patient with a thickened pituitary stalk (TPS) and papillary thyroid carcinoma (PTC) whose diagnosis remained obscure until a skin lesion appeared. The patient presented with PTC, status postthyroidectomy, and I131 therapy. PTC molecular testing revealed BRAF mutant (V600E, GTC>GAG). She had a 5-year history of polyuria/polydipsia. Overnight dehydration study confirmed diabetes insipidus (DI). MRI revealed TPS with loss of the posterior pituitary bright spot. Evaluation showed hypogonadotropic hypogonadism and low IGF-1. Chest X-ray and ACE levels were normal. Radiographs to evaluate for extrapituitary sites of Langerhans Cell Histiocytosis (LCH) were unremarkable. Germinoma studies were negative: normal serum and CSF beta-hCG, alpha-fetoprotein, and CEA. Three years later, the patient developed vulvar labial lesions followed by inguinal region skin lesions, biopsy of which revealed LCH. Reanalysis of thyroid pathology was consistent with concurrent LCH, PTC, and Hashimoto’s thyroiditis within the thyroid. This case illustrates that one must be vigilant for extrapituitary manifestations of systemic diseases to diagnose the etiology of TPS. An activating mutation of the protooncogene BRAF is a potential unifying etiology of both PTC and LCH.